Exploring the relationship of the physical environment with the perceived quality of care and well-being of the ageing people in nursing homes in Davao City - De Jesus, Ma. Lorraine O. (2019)
The study was conducted to promote an improved high-quality physical environment through exploring its relationship with the quality of life of the ageing people in the existing nursing homes. An environment that can support the cognitive and physical frailties of the ageing people, who are at risk of experiencing low levels of well-being due to their increased disabilities. A combination of cross-sectional, quantitative and qualitative approach was used to analyze the data of the research. There were six nursing homes involved that were grouped according to the bed capacity with small having less than thirty-one beds, medium having thirty-one to forty beds, and large having forty-one or more beds to ensure variation on the physical characteristics. The respondents were purposely sampled, which are the capable ageing people only, to ensure the reliability of the answers. The observational assessment tool used for the quality of the physical environment is the ?Sheffield Care Environment Assessment Matrix (SCEAM) Tool? while the tool used to measure the ageing peoples? quality of life in the existing nursing homes are: for the well-being is the ?Well-Being Index (WHO-5)? and ?Pleasant Events Schedule-AD (PES-AD)?; for the perceived quality of care is the ?Person-centered Climate Questionnaire (PCQ-P)?; and for the dependency level is the ?Cliffton Assessment Procedures for the Elderly-Behavior Rating Scale?. The results show from the bivariate analysis that the three building domains from the physical environment assessment namely: Comfort, Openness and Integration, and Choice, have a significant correlation with the residents? quality of life. There is a need to improve on these building domains for the physical environment to have a positive effect on the ageing people. Specifically, to increase: the comfort building domain: provide sensory stimulation spaces; the choice building domain: presence of different types and model of chairs and sofas; the openness and integration domain: vastness of open spaces, landscapes and green spaces.